Acute malnutrition among children aged 6-59 months of the nomadic population in Hadaleala district, Afar region, northeast Ethiopia - Zemichael Gizaw; Wondwoson Woldu; Bikes Destaw Bitew (BMC, 2018)
Abstract Background Acute malnutrition to be a major health burden in the world, particularly in the developing world. Acute malnutrition is associated with more than one third of the global disease burden for children. Malnourished children are physically, emotionally and intellectually less productive and suffer more from chronic illnesses and disabilities. The nature, magnitude and determinants of acute malnutrition are determined among the general populations; however, there is a lack of evidence in the nomadic communities. Methods A cross-sectional study was conducted to assess the magnitude and factors associated with acute malnutrition among children aged 6-59 months in Hadaleala district, Afar Region. A total of 591 under-five children were included in this study, and subjects were recruited by the multistage cluster sampling technique. Data were collected by a pre-tested questionnaire and a simple anthropometric index so called mid-upper arm circumference (MUAC). The multivariable binary logistic regression analysis was used to identify factors associated with acute malnutrition on the basis of adjusted odds ratio (AOR) with 95% confidence interval (CI) and p < 0.05. Results The prevalence of acute malnutrition was 11.8% (95% CI = 9.3, 14.8%). The highest prevalence (50%) of acute malnutrition occurred among children aged between 12.0-23.0 months. Childhood acute malnutrition was associated with the presence of two (AOR = 2.49, p < 0.05) and three (AOR = 12.87, p < 0.001) children in each household, unprotected drinking water sources (AOR = 3.78, p < 0.05), absence of the latrine (AOR = 5.24, p < 0.05), hand washing with soap (AOR = 0.21, p < 0.05), childhood diarrheal disease (AOR = 2.72, p < 0.05), and child vaccination (AOR = 0.15, p < 0.001). Conclusion The prevalence of acute malnutrition among children aged 6-59 months was was higher than the national prevalence. The number of children in each household, drinking water sources, latrine availability, hand washing practice before food preparation and child feeding, childhood diarrheal disease, and child vaccination were identified as factors affecting the childhood acute malnutrition in the nomadic community. Protecting drinking water sources from possible contaminants, improving hand washing practices, utilization of latrine, preventing diarrheal diseases and vaccinating children integrated with the access of nutrition education is important to improve nutrition of children of the nomadic people.